Association of NOTCH3 Variant Position With Stroke Onset and Other Clinical Features Among Patients With CADASIL. (2nd August 2022) - Cho, Bernard P.H.; Jolly, Amy A.; Nannoni, Stefania; Tozer, Daniel; Bell, Steven; Markus, Hugh S.
Abstract : Background and Objectives: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is caused by a cysteine-altering variant in 1 of the 34 epidermal growth factor-like repeat (EGFR) domains of the NOTCH3 protein. CADASIL has a variable phenotypic presentation, and NOTCH3 variants in EGFRs 1–6 have been found correlated with greater disease severity. We examined clinical and radiologic features and performed bioinformatic annotation of variants in a large CADASIL cohort to further understand these associations. Methods: We examined the association of NOTCH3 variant position on stroke onset and other clinical features among patients with CADASIL from the United Kingdom. We also explored how in silico predicted protein aggregation differed by variant position and the extent to which this affected stroke risk. Results: We identified 76 different cysteine-altering NOTCH3 variants in our cohort of 485 patients (mean age: 50.1 years; % male: 57.5). After controlling for cardiovascular risk factors, variants in EGFRs 1–6 were associated with earlier onset of stroke (hazard ratio [HR]: 2.05, 95% CI: 1.43–2.94) and encephalopathy (HR: 2.70, 95% CI: 1.15–6.37), than variants in EGFRs 7–34. Although the risk of stroke was higher in the patients with predicted protein aggregation (HR: 1.50, 95% CI: 1.05–2.14), this association was no longer significant after controlling for variant site. Further analysis suggested that lower stroke risk was observed for variants in EGFRs 10–17 compared with variants in the other EGFR domains. Discussion: NOTCH3 variant position is a predictor of stroke and encephalopathy in CADASIL independent of cardiovascular risk factors. Lower stroke risk was found for variants in EGFRs 10–17. Molecular factors that influence CADASIL disease severity remain to be determined.